Emerging Trends in Food Consumer Behaviour - Claudiu Coman; Ecaterina Coman; Teodor Florin Cilan (Amfiteatru Economic, 2025)
Changes in consumer behaviour are shaping food industry strategies, and a broad analysis of the specialised literature is needed to provide a holistic view of trends in consumer behaviour trends. This article aims to identify the research directions in the field and the trends that could shape food markets. Through a bibliometric analysis of 947 publications indexed in the Web of Science over the past five years, five major research directions were identified and, for each of them, emerging trends were established. Key findings reveal a growing emphasis on health, sustainability and digitalisation. Consumers are demanding organic, locally sourced, healthier products due to concerns about environmental impact and personal well-being. Digital tools are transforming food consumption patterns, but innovative technologies, such as drone delivery and food innovations, 3D printed food, insect-based products or other alternative proteins, still face consumer resistance. Packaging innovations, including active and edible packaging, offer the potential to improve food quality and sustainability and change consumer behaviour. The study emphasises the importance of social norms, health consciousness and social media in shaping purchase intentions for sustainable products. This analysis offers valuable insights for academia, industry, and policymakers to anticipate market changes and effectively adapt to evolving consumer demands